Analyzing the Effect of Bandage and Bracing on Stability Indices of Single Leg Stance in Patients with Ankle Sprain - Amin Behdarvandan; Mouhamad Jafar Shaterzadeh Yazdi; Shahin Goharpey; Reza Salehi (Majalah-i ̒ilmī pizishkī-i jundī/shapūr)
Background and Objective: In spite of the prevalence of ankle sprain , little objective data exist regarding the effect of sensory and motion restriction properties of external ankle supports on ankle sensory motor processes of ankle sprained patients. Subjects and Methods: In the present study, the effects of elastic bandage and rigid brace which had no sensory influence were evaluated for 28 patients. Ankle complex motor performance was measured using the Biodex Balance System.Results: Results showed that rigid brace had no effects on stability indices but the use of elastic bandage improved motor performance of ankle complex as evidenced by the decrease in overall (P= 0.004) and AP(P=0.010) stability indices.Conclusion: In patients with functional ankle instability external supports used improved ankle sensorymotor functions possibly because of elevated sensory inputs.